2015
DOI: 10.1017/s2040174415001476
|View full text |Cite
|
Sign up to set email alerts
|

Exposures influencing total IgA level in colostrum

Abstract: Immunoglobulin A (IgA) is a predominant immunoglobulin present in human breast milk and is known to play an important role in infant gut immunity maturation. Breast milk composition varies between populations, but the environmental and maternal factors responsible for these variations are still unclear. We examined the relationship between different exposures and levels of IgA in colostrum. The objective of this study was to examine whether exposures analysed influence levels of IgA in colostrum. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Smoking cessation was proposed to induce changes in the composition of the intestinal microbiota similar to the differences reported between obese and lean humans and was also proposed to influence the individual’s weight gain 45 . Even though all mothers but one ceased smoking during pregnancy, the extended associations found in the initial microbial colonizers in their offsprings could have been introduced via the entero-mammary pathway 46 or enhanced via the epigenetically modified compounds in breast milk 47 , 48 . More importantly, however, seven infants born to prior-smokers, also demonstrated higher BMI at birth (p = 0.022), lower BMI Z 1i -Z 0i (p = 0.030) and higher WG Z (12–3) (p = 0.032), which even exceeded + 0.67 cut-off in five infants and thus may predispose them to later obesity risk 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation was proposed to induce changes in the composition of the intestinal microbiota similar to the differences reported between obese and lean humans and was also proposed to influence the individual’s weight gain 45 . Even though all mothers but one ceased smoking during pregnancy, the extended associations found in the initial microbial colonizers in their offsprings could have been introduced via the entero-mammary pathway 46 or enhanced via the epigenetically modified compounds in breast milk 47 , 48 . More importantly, however, seven infants born to prior-smokers, also demonstrated higher BMI at birth (p = 0.022), lower BMI Z 1i -Z 0i (p = 0.030) and higher WG Z (12–3) (p = 0.032), which even exceeded + 0.67 cut-off in five infants and thus may predispose them to later obesity risk 8 .…”
Section: Discussionmentioning
confidence: 99%
“…While the exact function of IgA in human milk is unknown, it is thought to supplement infant IgA production, which only commences after birth ( 78 , 81 ). Data from several studies support a role for maternal environment (geographic location, microbial pressure, exposure to farm animals and cats) in driving milk IgA levels and specificity ( 40 , 41 , 82 ). Some studies have shown a link between high IgA levels and protection for the development of atopic dermatitis ( 41 , 51 ) while other studies show no link between sIgA and development of other atopic diseases ( 41 , 50 , 54 ).…”
Section: Immunoglobulin a (Iga)mentioning
confidence: 97%
“…Hence, sIgA in colostrum has been likened to an immune booster, a beneficial attribute that varies by maternal characteristics and can be impacted by medical intervention. Residual country variation in colostrum sIgA levels has been reported, even after accounting for collection time, and maternal parity, smoking, fruit and fish consumption, and allergen sensitization [ 323 ]. Cesarean delivery was independently associated with reduced sIgA colostrum levels in this study.…”
Section: Human Milk Composition and Allergymentioning
confidence: 99%